Smart Helmet As Driving Safety - Sri Kusumastuti; Sindung Hadwi Widi Sasono (Politeknik Negeri Semarang, 2023)
One of the common causes of accidents is physiological factors such as drowsiness. AÂ helmetÂ is a device used to reduce the risk of head injury when an accident occurs while driving. Helmets placed on motorbikes often experience theft to the detriment of the helmet owner. A helmet was created to reduce the risk of an accident, warn motorists when they are drowsy, and provide a warning when a helmet is stolen. The method begins with designing devices, preparing devices, testing, repairing, and adjusting devices. The main components used are Arduino Nano and Arduino Pro Mini. The input components are a pulse sensor, MPU6050 sensor, touch switch, NRF24L01 receiver, rope clip, on/off push button, and limit switch. The output components are one channel relay, NRF24L01 transmitter, and speakers. From the results of testing the device, the helmet will be connected to the motorbike if appropriately used, the speaker will send a rest notification if the rider is drowsy, and the helmet alarm will sound loud when someone wants to steal the helmet.